Alain Touraine en la ciudad de Santiago - Macari, Mirko (La Sociología en sus Escenarios, 2009)
Abstract. Between seminaries full, conferences and suppers top has passed by Santiago this intellectual to whom attributes paternity to him in the renovation of the Creole left. Without complexes it said that Santiago is ugly, the Chileans we are sad and is enough to agree with cart wheels. The French does not clear the brave thing. Resumen. Entre seminarios full, conferencias y cenas top ha pasado por Santiago este intelectual a quien se le achaca paternidad en la renovación de la izquierda criolla. Sin complejos dijo que Santiago es feo, los chilenos somos tristes y basta de comulgar con ruedas de carreta. Lo francés no quita lo valiente.